Model of Potential Strengthening and The Role of Family in Control and Modification of Risk Factors in Adult Women with Coronary Heart Disease - Suryaningsih; Fitriah; Rodiyatun; Musthofa Haris; May M. Peralta-Mendinueto (International Journal of Advanced Health Science and Technology, 2022)
Coronary heart disease is one of the non-communicable diseases with the highest prevalence in Indonesia. Coronary heart disease incidents can be prevented by controlling modifiable Coronary heart disease risk factors. Family is the strength for a person to survive pressure or keep life in balance. The purpose was to analyze the effect of strengthening family potency on the control of modifiable coronary heart disease risk factors in adult women. The research design used a quasi-experimental. The research variable was Coronary heart disease risk control models. The population in this study were families who had adult female family members with coronary heart disease in the work area of Arosbaya Public Health Center in 2019. In the sample in this study, as many as 30 people in each group were taken by simple random sampling. The research instrument used a simulation model for controlling Coronary heart disease risk factors that can be modified for women by the family using modules. Analysis used the Kolmogorov Smirnov and pair t-tes. The results showed that the mean modification of Coronary heart disease risk factors in adult women increased, except for avoidance of cigarette smoke (p <0.05). The pair t-test results show that there is a difference in controlling the risk factors for Coronary heart disease that can be modified after strengthening family potential, except for the avoidance of cigarette smoke. It can be concluded that the implementation of the family potential strengthening model is proven to significantly increase the family's ability to control the risk factors for Coronary heart disease can be modified in adult women. It is recommended that Coronary heart disease in adult women can be carried out by controlling risk factors that can be modified by involving all family components